Evaluation of kinetic and kinematic variables during a countermovement jump to assess neuromuscular status in team-sport ahtletes - Balloch, A. S. (Journal of Australian Strength and Conditioning, 2018)
The primary purpose of this literature review was to evaluate the effectiveness of a variety of kinetic and kinematic variables associated with a countermovement jump (CMJ) in detecting the presence of neuromuscular fatigue (NF) and tracking the time-course of recovery in team-sport athletes. Additionally, the neurological and metabolic mechanisms associated with stretch-shortening cycle (SSC) dysfunction contributing to NF as a consequence of exhaustive intermittent exercise has also been discussed. A search of existing literature was conducted using Google Scholar and SPORTDiscus scholarly search engines linked with the Edith Cowan University database. Original research within the past decade (>2007) that implemented a countermovement jump protocol to assess the neuromuscular response to a bout of competition or match simulated training in team-sport athletes was the primary focus. The key findings of this review indicate that a typical CMJ analysis focusing on performance metrics during the push-off phase of a CMJ may not be sensitive enough to accurately detect the presence of NF and track the time-course of recovery. Instead, NF may manifest as an altered movement strategy due to impaired SSC function, and therefore, a more comprehensive analysis encompassing both push-off and countermovement portions of a CMJ may better signify neuromuscular status and the typical bi-phasic restoration of SSC properties. Eccentric loading patterns along with jump duration and a flight time to contraction time ratio (FT:CT) may best reveal the presence of NF as a reduction in movement economy. However, the lower reliability associated with some of these kinetic and kinematic measures must also be considered. Identification of fatigue induced shifts in movement strategy coordinated by the neuromuscular system may enhance monitoring protocols and reduce the risk of subsequent injury.